Do undergraduate psychology statistics textbooks make connections to their underlying epistemological basis? - Kingston, Neal M.; Wilson, Taylor D.; Quintana, Rafael; Peng, Anqi (Frontiers in Psychology, 2025)
Quantitative methods in psychology have been a source of controversy for decades. When misapplied or misinterpreted, they can provide a false sense of objectivity and/or lead to faulty inferences, impeding the progress of psychological research. Moreover, misunderstanding and misinterpretation of certain quantitative methods is rampant, even among trained practitioners and researchers. Epistemology is the philosophical discipline regarding how one can establish knowledge. As such, it is the foundational basis of all research methodology. This article evaluates the current state of undergraduate psychology statistics textbooks to see if they provide a proper epistemological basis necessary to support statistical reasoning. The hope is to identify opportunities to improve the methodological understanding of future generations of psychologists.